Prompt gamma neutron activation analysis of boron with a 241 Am-Be neutron source - Turhan, Şeref; Yücel, H.; Demirbaş, A. (Journal of Radioanalytical and Nuclear Chemistry, 2004)
A prompt gamma neutron activation analysis (PGAA) setup installed at ANRTC has been used to analyze boron. It consists of a 22.6% REGe detector and a 740 GBq 241AmñBe neutron source moderated with water and paraffin. At the sample irradiation position, the thermal neutron fluence rate measured was 2.36. 104 n. mñ2. sñ1 and the corresponding Cd-ratio was 22 for gold monitor. The absolute detection efficiency in the range of 120ñ1500 keV was determined using 152Eu standard solution. The sensitivity and detection limit for standard boric acid samples has been determined. The boron content in boric acid prepared from Turkish borate ores is measured to be 15.91±0.46% wt.